Hydrogen Chemisorption on Singly Vanadium‐Doped Aluminum Clusters. Issue 62 (13th October 2017) - Vanbuel, Jan; Fernández, Eva M.; Ferrari, Piero; Gewinner, Sandy; Schöllkopf, Wieland; Balbás, Luis C.; Fielicke, André; Janssens, Ewald
Abstract: The effect of vanadium doping on the hydrogen adsorption capacity of aluminum clusters (Al n +, n =2–18) is studied experimentally by mass spectrometry and infrared multiple photon dissociation (IRMPD) spectroscopy. We find that vanadium doping enhances the reactivity of the clusters towards hydrogen, albeit in a size‐dependent way. IRMPD spectra, which provide a fingerprint of the hydrogen binding geometry, show that H2 dissociates upon adsorption. Density functional theory (DFT) calculations for the smaller Al n V + ( n =2–8, 10) clusters are in good agreement with the observed reactivity pattern and underline the importance of activation barriers in the chemisorption process. Orbital analysis shows that the activation barriers are due to an unfavorable overlap between cluster and hydrogen orbitals. Abstract : The straight dope : The adsorption of hydrogen onto small vanadium‐doped aluminum clusters was studied experimentally by a combination of mass spectrometry and infrared mulitple photon dissociation spectroscopy. Dissociative chemisorption was found, though with size‐dependent activation barriers that could be explained by the molecular orbital symmetry of the frontier orbitals of the molecularly bound complexes.